Baju Kurung Pakaian Tradisional Perempuan Melayu Jambi - Fatonah Nurdin; Hartati Hartati; Selfi Mahat Putri (Universitas Batanghari Jambi, 2020)
This research would focus on studying of Jambi Malay Culture from the point of view baju kurung as the traditional clothing of Jambi Malay women. By using qualitative research methods with a historical approach, this study aimed to determine the history and meaning of the philosophical values of baju kurung with its development ethically and aesthetically as the traditional clothing of Jambi Malay women. The benefits of this research were expected to become an inventory of Jambi Malay culture in the scientific studies. In the background of the diversity of natural and cultural wealth owned by Jambi province, there were many kinds of values of beauty, philosophy and cultural ethical and aesthetic values, one of them was an aesthetics in clothing which was important part of traditional Jambi Malay women's clothing. Baju kurung as a symbol of Jambi Malay Muslimah women have a philosophical meaning that was closely related to traditional and Islamic customs. The entry of Islam in the land of Malay Jambi influenced the concept of dressing up in Jambi's Malay women. It can be concluded that baju kurung was a reflection of the identity of Muslimah women in Jambi, according to Islamic law, which is described in the seloko of custom Jambi